The Digital Dilemma: How Cyberloafing and Work Discipline Shape Generation Z Employee Performance in Bandung - Syawali, Iska Alma; Sary, Fetty Poerwita (Jurnal Locus Penelitian dan Pengabdian, 2025)
The incidence of cyberloafing among Generation Z workers, combined with poor work discipline, is a cause for concern regarding workplace productivity. Research indicates that individual internet use is highest at the start and end of working hours, which implies that patterns of digital engagement could impact performance. This study explains the impact of cyberloafing and workplace discipline on employee performance of Generation Z employees in Bandung City using quantitative techniques with Structural Equation Modeling (SEM) of survey data of 140 employees. The findings show that cyberloafing has a positive impact on employee performance (path coefficient: 0.255, T-statistic: 2.977, P-value: 0.003), which could be taken as a mental break to enhance productivity. Work discipline has a greater positive impact (path coefficient: 0.569, T-statistic: 8.202, P-value: 0.000), highlighting its significant role in workplace efficiency. The model explains 34.1% of employee performance is determined by Cyberloafing and Work Discipline (R² = 0.341). This study refutes the belief that cyberloafing merely hinders productivity, as it can have positive impacts when controlled. Organizations would have to reassess strict internet policies and allow reasonable cyberloafing as mental relaxation while enforcer organized control to optimize effectiveness. These views lead HR professionals to strike a balance between efficiency and employee convenience in the cyberspace workplace.